2020
DOI: 10.1108/bfj-09-2020-0769
|View full text |Cite
|
Sign up to set email alerts
|

Plant protection practices: how do risk perception, subjective and objective knowledge influence the preference of German consumers

Abstract: PurposeThe purpose of this paper is to identify which plant protection practices consumers prefer and why. The authors focused on beneficial insects, genetically modified (GM) plants, synthetic chemical pesticides, biological plant protection, mechanical-physical plant protection as well as biotechnical plant protection. The authors studied the effects of the risk perception and both subjective and objective knowledge on preference.Design/methodology/approachThe authors collected cross-sectional data from n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This once again showed that individual psychological factors are the key link connecting their cognition and behavior [63,64]. Meanwhile, it also further revealed the internal influence process of risk perception difference on behavior [35][36][37]. That is, the differentiated perceptions can positively stimulate the subject's learning willingness, and then promote the formation of information adoption behavior, which deepens the current research on the effect of risk perception difference.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This once again showed that individual psychological factors are the key link connecting their cognition and behavior [63,64]. Meanwhile, it also further revealed the internal influence process of risk perception difference on behavior [35][36][37]. That is, the differentiated perceptions can positively stimulate the subject's learning willingness, and then promote the formation of information adoption behavior, which deepens the current research on the effect of risk perception difference.…”
Section: Discussionmentioning
confidence: 77%
“…From the perspective of the risk management process, it is manifested as cognitive differences in risk sources, probability of occurrence, degree of impact, and confidence in dealing with it. As a cognitive element, risk perception is the result of an individual's judgment on the connotation and value of risk information and can further affect an individual's behavior and preferences [35][36][37]. On the other hand, information adoption is a process in which the subject selects, evaluates, accepts, and utilizes information purposefully [38].…”
Section: Risk Perception Difference and Information Adoption Behaviormentioning
confidence: 99%
“…Objective knowledge is stored in the consumers’ long-term memory and is usually assessed through testing [ 48 , 49 ]. In contrast, subjective knowledge is based on direct experience by consumers and their interpretation of these experiences [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, organic versus conventional agricultural management practices (Cristache et al 2018, Gomiero, 2012). • Some food cultures are more likely to rely on traditional methods of preserving or preparing food, which can increase the risk of pests and diseases (Lehberger and Becker, 2020). For instance, the use of some types of fermentation using soy sauce and miso (Skowron et al, 2022).…”
mentioning
confidence: 99%